Overcoming Challenges in STEM Education: A Literature Review That Leads to Effective Pedagogy in STEM Learning - Suhirman Suhirman; Saiful Prayogi (Postgraduate, University of Mataram, 2023)
The current study aims to analyze trends in studies related to challenges of STEM-based learning, analyzing the challenges of STEM education, describing solution approaches to overcome challenges in STEM education, and describing effective STEM pedagogy. To achieve the goals of this study, a literature review related to STEM education and learning was conducted, specifically by performing a bibliometric analysis. The bibliometric analysis is related to a coherent literature review with the theme of